2004
DOI: 10.1158/0008-5472.can-03-0245
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Receptor Tyrosine Kinase Axl Promotes Ocular Melanoma Cell Survival

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 47 publications
4
51
0
Order By: Relevance
“…In the present study, we confirm that overexpression of MZF1 is tumorigenic, and for the first time, we report that MZF1 induces tumor growth and metastasis through the transactivation of Axl, thus adding to the molecular targets and mechanisms that can mediate an oncogenic potential of MZF1 in epithelialderived tissues. Axl has been reported as a transforming gene (21) that is overexpressed in several tumors (22)(23)(24)(25)(26)(27), and the Gas6/Axl signaling pathway is known to induce cell proliferation, antiapoptosis, migration, invasion, and angiogenic processes, which are most likely mediated through Ras, Src, mitogen-activated protein kinase/extracellular signal-regulated kinase, phosphoinositide 3-kinase/Akt, and NF-κB signaling pathways (14,15,19,29,31,32,(44)(45)(46)(47)(48)(49). However, still further studies are needed to enhance the understanding of the downstream components of the Gas6/Axl signaling axis in tumor formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we confirm that overexpression of MZF1 is tumorigenic, and for the first time, we report that MZF1 induces tumor growth and metastasis through the transactivation of Axl, thus adding to the molecular targets and mechanisms that can mediate an oncogenic potential of MZF1 in epithelialderived tissues. Axl has been reported as a transforming gene (21) that is overexpressed in several tumors (22)(23)(24)(25)(26)(27), and the Gas6/Axl signaling pathway is known to induce cell proliferation, antiapoptosis, migration, invasion, and angiogenic processes, which are most likely mediated through Ras, Src, mitogen-activated protein kinase/extracellular signal-regulated kinase, phosphoinositide 3-kinase/Akt, and NF-κB signaling pathways (14,15,19,29,31,32,(44)(45)(46)(47)(48)(49). However, still further studies are needed to enhance the understanding of the downstream components of the Gas6/Axl signaling axis in tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Gas6 binds to TAM family members with different affinities. Gas6 was first discovered as an upregulated gene in growth-arrested cells (12), and further studies with Gas6 signaling suggested its role in cell survival (13,14), proliferation (15,16), stimulation of cell migration (17), and cell-cell adhesion through Axl (18). Intracellular signaling of Axl is also activated by its homophilic and heterophilic interactions (19), mediated mainly by a multisubstrate docking site (20).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, TAM receptors have also been shown to increase proliferation without inhibiting apoptosis (Sainaghi et al, 2005). A third situation exists, whereby TAM receptors promote both survival and proliferation (van Ginkel et al, 2004). Each mechanism provides a means by which TAM receptors may contribute to tumor growth.…”
Section: Cell Survival and Tumor Growthmentioning
confidence: 99%
“…Overexpression of Axl can transform fibroblasts even in the absence of a ligand (Burchert et al, 1998). Axl is known to induce cell survival (Melaragno et al, 2004;van Ginkel et al, 2004), proliferation (Stenhoff et al, 2004;Sainaghi et al, 2005), stimulation of cell migration and cell-cell adhesion (McCloskey et al, 1997). Moreover, an increased expression of Axl is associated with invasion, metastasis, angiogenesis, and is found in metastatic colon, prostate carcinoma, gastric and endometrial cancers, breast cancers, lung cancers and sarcomas (Hafizi and Dahlback, 2006).…”
Section: Introductionmentioning
confidence: 99%